2021
DOI: 10.1080/07853890.2021.1938662
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of women towards products containing hormones (hormonal contraceptives or hormone therapy): what changes from pre to postmenopause?

Abstract: Facchinetti (2021) Attitudes of women towards products containing hormones (hormonal contraceptives or hormone therapy): what changes from pre to postmenopause?,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…In our study, both healthy women and those with LS showed a wrongly negative perception related to the use of CHCs and the risk of developing endometrial cancer. These results confirmed the lack of awareness about the benefit of using CHCs on preventing endometrial cancer reported also in the general population by a previous study [ 12 ]. However, women with LS had a significantly more negative opinion on this matter compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, both healthy women and those with LS showed a wrongly negative perception related to the use of CHCs and the risk of developing endometrial cancer. These results confirmed the lack of awareness about the benefit of using CHCs on preventing endometrial cancer reported also in the general population by a previous study [ 12 ]. However, women with LS had a significantly more negative opinion on this matter compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, in daily practice, myths and taboos regarding side effects and long-term consequences of CHC use on women’s health need to be fully addressed also in the general population [ 12 ]. The awareness of the effects of hormonal therapies in women at high risk of developing endometrial cancer, colorectal, or ovarian cancer, such as those affected by LS, is even more limited, with few published studies addressing the perception about benefits and risks related to CHCs only in BRCA pathogenic variant carriers [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the age-related issues associated with the use of hormonal therapies must be analysed. 12 Importantly, among them is the increased risk of cancer, the possible occurrence of osteopenia and osteoporosis, the risk of thromboembolism, psychological changes and the possible sexual dysfunction associated with this peculiar late reproductive period. 13 Regarding the thromboembolic risk, it is strictly related to hypertension and cardiovascular diseases in general, as well as obesity and metabolic syndrome, whose incidence rises with age.…”
Section: Contraception In Perimenopause: Is There Need or Not?mentioning
confidence: 99%